On rit au NarKomPros : Anatoli Lounatcharski et la théorie du rire soviétique - Gérin, Annie (RACAR : Revue d'art canadienne / Canadian Art Review, 2012)
In 1930 Anatoly Lunacharsky, Soviet Commissar of Enlightenment from 1917 to 1929, set up a government commission to study satirical genres in the visual arts, literature, music, theatre, and film. At the same time, he was working on the manuscript for a book entitled The Social Role of Laughter, which he never completed. Throughout his career as Commissar, Lunacharsky was instrumental in producing much satirical work through government contracts and commissions allocated to artists. During those years he also wrote art criticism and theoretical texts that encouraged Soviet artists to use humour and satire as a tool for social criticism and change in the context of the emerging Soviet Union. These writings were inspired by the prevalent theories of laughter (mainly those of Freud, Bergson, Spencer, Sully, and Lipps), revisiting them through the lens of Marxism, and translating them into a very specific Soviet language and worldview. Although they were published in Soviet journals, they remain virtually unknown. This essay examines Lunacharsky’s theoretical contribution to the study of laughter and its influence on the production of visual satire in the first decades of the Soviet Union.